2021
DOI: 10.3390/ma14226861
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration Potential of Biodentine: A Systematic Review

Abstract: The aim of this systematic review is to investigate the teeth discoloration potential of Biodentine. An electronic search in six databases (PubMed, Cochrane Library, LILACS, SCIELO, Web of Science, and Scopus) was conducted by three independent reviewers to identify eligible articles. The following search terms were used: ((discolo*, staining potential, color, colour, or spectrophotomet*), (teeth or tooth), and (Biodentine)). Methodology following the PRISMA (Preferred Reporting Items for Systematic Reviews an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
4
0
1
Order By: Relevance
“…Mineral trioxide aggregate is most commonly applied onto the clot, but discoloration may be an undesirable side effect, in particular if the radiopacifier is bismuth oxide (Marciano et al, 2015). Biodentine, a laboratory grade tricalcium silicate cement that uses zirconium oxide as radiopacifier, appears to evoke less discoloration; however, the contact with blood is a critical factor (Slaboseviciute et al, 2021). Discoloration of teeth, especially of anterior teeth, should be reported as one of the outcome parameters after revitalization (Kahler & Rossi‐Fedele, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mineral trioxide aggregate is most commonly applied onto the clot, but discoloration may be an undesirable side effect, in particular if the radiopacifier is bismuth oxide (Marciano et al, 2015). Biodentine, a laboratory grade tricalcium silicate cement that uses zirconium oxide as radiopacifier, appears to evoke less discoloration; however, the contact with blood is a critical factor (Slaboseviciute et al, 2021). Discoloration of teeth, especially of anterior teeth, should be reported as one of the outcome parameters after revitalization (Kahler & Rossi‐Fedele, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, o contato do óxido de bismuto com hipoclorito de sódio também leva à descoloração. Slaboseviciute, et al, (2021)…”
Section: Discussionunclassified
“…TheraCal LC releases calcium, which increases the development of hydroxyapatite and, consequently, dentinal bridges. Ghoddusi et al [66] evaluated the physicochemical parameters of ProRoot MTA, TheraCal, and Dycal and determined that TheraCal had a greater calcium-releasing capacity and lower solubility than ProRoot MTA and Dycal. [67] According to a study, TheraCal demonstrated superior bonding capacity to composite or glass-ionomer cements than Biodentine.…”
Section: Endosequence Root Repair Materials (Errm )mentioning
confidence: 99%